Terminal freeze [compact disc, unabridged] - Child, Lincoln (Child, Lincoln. Jeremy Logan series., 2009)
A group of scientists sponsored by a major media conglomerate are sent on an expedition to Alaska's Federal Wilderness Zone, one of the most remote places on Earth. When the group makes an astonishing find, an ancient animal encased in solid ice that appears to be a giant cat, the parent company quickly plans the ultimate spectacle, the animal will be cut from the ice, thawed, and revealed on live television. Ignoring the dire warnings of a local Eskimo group, the scientists make one more horrifying discovery: the beast is no cat ... it's an ancient killing machine. And it may not be dead.